Distinct Variations in Gene Expression and Cell Composition across Lichen Planus Subtypes - Knoch, Cadri; Baghin, Veronika; Turko, Patrick; Winkelbeiner, Nicola; Staeger, Ramon; Wei, Kongchang; Banzola, Irina; Mellett, Mark; Levesque, Mitchell P.; Kuendig, Thomas; French, Lars E.; Heinzerling, Lucie; et al. (International Journal of Molecular Sciences, 2024)
Lichen planus (LP) is a highly prevalent inflammatory skin disease. While various clinical subtypes have been defined, detailed comparisons of these variants are lacking. This study aimed to elucidate differences in gene expression and cellular composition across LP subtypes. Lesional skin biopsies from 28 LP patients (classical, oral, genital, and lichen planopilaris) and seven non-diseased skin controls (NDC) were analyzed. Gene expression profiling of 730 inflammation-related genes was conducted using NanoString. Immune cell compositions were assessed by multiplex immunohistochemistry. Gene expression profiles revealed unique inflammatory signatures for each LP subtype. Lichen planopilaris exhibited the most divergence, with downregulated gene expression and upregulation of complement pathway genes (C5-7), along with elevated M2 macrophages. Oral and genital LP demonstrated similar profiles with strong upregulation of TNF-related and Toll-like receptor-associated genes. Oral LP showed the highest upregulation of cytotoxicity-associated genes, as well as high numbers of CD8+ IL-17A+ (Tc17) cells (8.02%). Interferon gene signatures were strongly upregulated in oral and classical LP. The study highlights distinct differences in inflammatory gene expression and cell composition across LP subtypes, emphasizing the need for tailored therapeutic approaches.
CRIS-Team Scopus Importer:2024-09-27
Keywords: immune cell infiltrate; lichen planus; lichen planus subtypes; multiplex immunohistochemistry; NanoString